FUNGSI PEMERINTAH DALAM PELAYANAN PUBLIK DI PUSKESMAS INDUK KECAMATAN KUBU KABUPATEN ROKAN HILIR TAHUN 2010-2013 - Novi Triayanti; Muhammad Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Government services essentially aims to create a fair and prosperous society both materially uniform and spiritually based on Pancasila in container country of the Republic of Indonesia which is free, united, sovereign and sovereign. Atmosphere nation safe, peaceful, or derly and dynamic as well as in the social environment of a free and friendly world. The government has an obligation to provide minimum health services nee ded by his people. For health care providers principles that must be followed in providing health services to the community is how people feel satisfied and comfor table in receiving health given the existence of health centers and as a medium to deliver health services to be executed so well that the quality of services provided in accordance with what is desired by the community.Based on the background of the problems described above, the researchers are interested in researching about “Government Function in Health Care The Health Clinic Kecamatan Kubu Kabupaten Rokan Hilir (2010-2013)”. Types used in this study qualitative descriptive survey techniques. The location of this research carried out at the health center Kecamatan Kubu Kabupaten Rokan Hilir. The informant is a person or group of people who have the knowledge, namely UPTD, head of the health center, business health centers, health centers Officer of Infrastructure, Community treatment.The results of this penerlitian namely; Services in health centers Kecammatan Kubu as described mentioned above, can be explained bring health care services, quality of service and comfort of the patient because the health center is located alongside a highway parent makes noise levels, as well as in referral health center personnel Parent seems slow in issuing a letter referral for patients who want to do a local hospital treatment or hospital you want to target, while it was in duty in case of problems due to the lack of expertise in the parent community health centers, because of the many workers who continue their education kejenjang D3 and S1, resulting in a low level of experts or nurse. Maximum services and facilities necessary to support adequate facilities and human resources are sufficient, but what happens in the parent Kubu Kecamatan Kubu health centers, there are some shortcomings, human resources are not enough to provide a good service to the community, where there is a double duty by someone in their work, while the facilities for treatment also experienced keterbatasana, while drugs are limited in number, and the building is not sufficient to provide excellent service.Keywords: Function, Government, Services, Health, Health Center Parent